2021
DOI: 10.3390/insects12040277
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Cerambycid Beetle Biodiversity in a Tropical Rainforest in Yunnan Province, China, Using a Multicomponent Pheromone Lure

Abstract: The Cerambycidae comprise a large and ecologically important family of wood-boring beetles. The purpose of this study was to examine the effectiveness of a generic lure as a potential monitoring tool. Working in a subtropical forest in southwest China, we set traps baited with generic lures at ground level (1 m) and canopy height (~18 m) across 22 randomly located forest plots (12 regenerating forest, 10 mature forest). Three stations were established per plot and each plot was trapped for 7 days in May–June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Our trapping produced two new species records for Idaho (Lyons-Yerion et al 2020a), and seven new species were recorded for Delaware in a similar study (Handley et al 2015). Our results provide additional support for using synthetic pheromone-baited trapping to study the cerambycid community, a method that has been used to assess cerambycid communities in several regions in North America and also in the Russian Far East, China, and Australia Sweeney et al 2014;Dodds et al 2015;Handley et al 2015;Hayes et al 2016;Schmeelk et al 2016;Rice et al 2020;Wickham et al 2021), which speaks to the technique's broad application for use in varying geographic regions.…”
Section: Outcomes and Future Worksupporting
confidence: 62%
“…Our trapping produced two new species records for Idaho (Lyons-Yerion et al 2020a), and seven new species were recorded for Delaware in a similar study (Handley et al 2015). Our results provide additional support for using synthetic pheromone-baited trapping to study the cerambycid community, a method that has been used to assess cerambycid communities in several regions in North America and also in the Russian Far East, China, and Australia Sweeney et al 2014;Dodds et al 2015;Handley et al 2015;Hayes et al 2016;Schmeelk et al 2016;Rice et al 2020;Wickham et al 2021), which speaks to the technique's broad application for use in varying geographic regions.…”
Section: Outcomes and Future Worksupporting
confidence: 62%
“…The attractants may also be useful for biological studies, such as biodiversity surveys and studies of population dynamics. However, because of the conserved status of these compounds among related taxa, and considering the uniqueness of the Chilean fauna and the potency of these attractants, care should be taken to avoid potential negative effects from using them extensively and intensively, in case of harm to beneficial, rare, or endangered species [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…180 described cerambycid species [21], most of which are native, including some economically important ones. Thus, if some of the known and widely conserved pheromones which have been identified from species in other parts of the world also proved to be attractive to species native to western South America, they could serve as valuable tools for basic and applied studies for such species [22][23][24][25][26]. Therefore, the objective of the work reported here was to test a variety of known cerambycid pheromones as possible attractants for species on the southwestern side of the Andes for future development of monitoring tools for cerambycid pests, but also for biological studies of the Chilean fauna.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that blends of synthesized longhorn beetle pheromone components can be used to attract multiple species simultaneously. For example, blends of longhorn beetle pheromones have been tested in France (Fan et al, 2019), Austria (Hoch et al, 2020), the USA (e.g., Hanks et al, 2012Hanks et al, , 2018Rice et al, 2020), and southern China (Wickham et al, 2014(Wickham et al, , 2021. Common components of these blends, in various combinations, have included pheromones of species in the subfamily Cerambycinae (racemic 3-hydroxyhexan-2-one, syn-2,-3-hexanediol and 2-methylbutan-1-ol), and pheromones of species in the subfamily Lamiinae including (E)-6,10-dimethylundeca-5,9-dien-2-ol (known as fuscumol), fuscumol acetate and 2-(undecyloxy)-ethanol (known as monochamol).…”
Section: Introductionmentioning
confidence: 99%
“…Common components of these blends, in various combinations, have included pheromones of species in the subfamily Cerambycinae (racemic 3-hydroxyhexan-2-one, syn-2,-3-hexanediol and 2-methylbutan-1-ol), and pheromones of species in the subfamily Lamiinae including (E)-6,10-dimethylundeca-5,9-dien-2-ol (known as fuscumol), fuscumol acetate and 2-(undecyloxy)-ethanol (known as monochamol). Blends of these and related compounds have recently been field tested in many areas of the world including in the USA (Hanks et al, 2012(Hanks et al, , 2018Miller et al, 2015), in Europe (Cavaletto, Faccoli, Marini, Spaethe, Magnani, & Rassati, 2020;Fan et al, 2019;Hoch et al, 2020), in Asia (Sweeney et al, 2014;Wickham et al, 2014Wickham et al, , 2021 and in South America (Gil et al, 2021).…”
Section: Introductionmentioning
confidence: 99%